Acute heart failure and rhabdomyolysis: a clue for the diagnosis of polymyositis with cardiac involvement - P. Pinto-Lopes; L. Carneiro-Leão; R. Morais; J. Pinheiro; A. Vieira Lopes; P. Bettencourt (PAGEPress Publications, 2017)
Polymyositis is an idiopathic inflammatory myopathy, characterized by proximal muscle weakness and sometimes extramuscular manifestations. We report the case of a 51-year-old male, with history of complete heart block, which required pacemaker implantation, and subsequently heart failure, presenting to the emergency department with worsening of dyspnea and peripheral edema. He was admitted to the Internal Medicine ward with acute heart failure and started on diuretic therapy. During hospitalization, he was discovered to have marked rhabdomyolysis. Examination revealed proximal symmetrical muscle weakness and arthralgia. The immunological study, electromyography and muscle biopsy confirmed polymyositis. The patient was started on prednisolone with clinical improvement and resolution of rhabdomyolysis. The presence of conduction defect, ventricular dysfunction, mitral valve regurgitation, segmental hypokinesia (myocardial scintigraphy without perfusion defects) and pulmonary hypertension, as well as elevated troponin with improvement after specific therapy, points to cardiac involvement. Polymyositis is a rare entity, with an insidious evolution and a myriad of extramuscular features that can mimic other conditions. In particular, cardiac involvement may be the first and only recognized manifestation. The key point for the diagnosis is to contemplate the possibility of polymyositis.